The Role of Human Resources in Islamic Education in the Era of Civil Society 5.0 - Badrus Syamsi; Zamroni Zamroni (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
The increased role of technology and the complexity of societal changes have ushered in a new era in education, known as Civil Society 5.0. This research aims to explore the role of Human Resources at MTs Darussalam Samarinda in adapting to the Civil Society 5.0 era. The research methodology employed a qualitative-descriptive approach, utilizing interview data from all available human resources within the madrasah. Observations were conducted in the field to validate the obtained data, both from interview transcripts and documents. Data analysis involved an interactive technique encompassing collection, condensation, presentation, and conclusion drawing. The research findings emphasize the pivotal role of Human Resources in adopting technology for learning, adjusting the curriculum to meet contemporary demands, and establishing robust collaborations within the local community. Islamic education Human Resources are not merely instructors; they also serve as change leaders, shaping students' characters, upholding religious values, and preparing students to actively engage in a dynamic society.